A short note for vaccine cold chain network models - Reong, Samuel; Hsiao, Yu-Lin; Wee, Hu-Ming (RSF Conference Series: Business, Management and Social Sciences, 2022)
Vaccine shortages in current COVID-19 pandemics have highlighted that vaccine production and distribution are resource-intensive processes. In addition to manufacturing new vaccines for emerging epidemics, existing stockpiles must be maintained as well. With limited resources available during this crisis, it is critical to identify efficient ways to utilize the scarce materials. To do so requires a better understanding of how vaccine supply chains are currently operating under normal and scarce circumstances, where supplies can be procured from multiple sources and stored at various locations before distribution to hospitals and clinics. This study seeks to determine what influences these network structures by assessing historical vaccine supply chain networks, including temperature levels, storage temperatures, transport methods, time delays, etc. By summarizing a bibliometric study of the Dimensions and Web of Science databases, the review is intended to enable researchers to identify optimal strategies for developing relevant vaccine production and distribution models.